Enhancing the teaching of science practicals in Tanzanian public secondary schools: A mixed-methods assessment of challenges - Sanjito, Baraka Peter; Hyams-Ssekasi, Denis (Indonesian Journal of Education and Pedagogy, 2025)
Laboratory work is essential for increasing students’ knowledge of science and improving their hand skills. However, in many secondary schools in Tanzania, especially in the Nyamagana District, teachers find it challenging to apply the curriculum's emphasis on conducting experiments in class. This study aimed to determine the challenges that prevent the effective use of science practicals in secondary education. In this study, questionnaires were administered to 64 science teachers, interviews were conducted with eight school heads, and lessons and laboratory areas were directly observed. Data analysis was done using descriptive statistics and thematic analysis. The difficulty in teaching science appears to have increased due to limited equipment, a shortage of materials, large student groups, high workloads, inadequate professional development, and a lack of laboratory technicians. To date, most institutions have not utilized virtual labs or other digital tools. For this reason, many educators teach students mainly through theory, making lessons diverge from the curriculum's goals. According to the study, three key factors are necessary for meaningful progress: upgrading infrastructure, providing staff with better training, and updating the curriculum to reflect reality and utilize technology more effectively. This research offers valuable insights applicable to Tanzania and other resource-constrained areas in the region.